Host factors for retroviral integration site selection. Issue 2 (February 2015) - Debyser, Zeger; Christ, Frauke; De Rijck, Jan; Gijsbers, Rik
Highlights LEDGF/p75 and BET are the targeting factors for lentiviral and gammaretroviral integration. Both chromatin-readers link the fate of the provirus with the epigenetic status of the chromatin. LEDGINs are novel antivirals that interfere with the interaction between HIV integrase and LEDGF/p75. Re-engineered LEDGF/p75 and BET tethers may open new avenues for safer gene therapy.